2011
DOI: 10.29333/ejgm/82692
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Temporal Bone CT With Surgery Findings in Evaluation of Chronic Inflammatory Diseases of The Middle Ear

Abstract: Aim: Computerized tomography (CT) examination of temporal bone is a routine procedure in the diseases of the middle ear. The aim of this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
5
19
2
Order By: Relevance
“…This is higher than findings by Suat Keskin et al (2011), [42] who found it in 54% of their patients [ Table 1]. …”
Section: Discussioncontrasting
confidence: 76%
“…This is higher than findings by Suat Keskin et al (2011), [42] who found it in 54% of their patients [ Table 1]. …”
Section: Discussioncontrasting
confidence: 76%
“…Incus was the most commonest ossicle to be involved. Incus was seen to be eroded in almost all cases of cholesteatoma [9], followed by stapes and malleus, in accordance with the findings of Keskin et al [18]. In CT Scan Malleus and body of incus are visualized easily.…”
Section: Ossicular Erosionsupporting
confidence: 72%
“…[16][17][18][19] Computed tomography detection of facial canal dehiscence has a sensitivity of 66-66.6 per cent and a specificity of 84-98 per cent. 20,21 Hence, it could be hypothesised that our second and third cases did actually have microdehiscences of the fallopian canal on the side of the development of their palsy, which were not obvious on their CT scans. This hypothesis is based on the present understanding that barotrauma in association with bony fallopian canal dehiscence is the most likely explanation for the observed facial palsy, despite the fact that two of our three patients had intact bony canals evident on their CT scan.…”
Section: Discussionmentioning
confidence: 99%